Solitary plasmacytoma of the metacarpal bone in an adolescent - Priya Mary Jacob; Rekha A. Nair; Sumod Mathew Koshy; Jayasree Kattoor (Wolters Kluwer Medknow Publications, 2014)
Solitary plasmacytoma of the bone (SPB) is a plasma cell neoplasm that usually presents as a lytic lesion mainly localized within the axial skeleton. The occurrence of SPB in young individuals is exceedingly rare, but has been sporadically reported before. We report a case of SPB involving metacarpal bone in a 16-year-old male with a prior history of trauma at the same site.